Economic costs and health utility values associated with extremely preterm birth: evidence from the EPICure2 cohort study - Achana, F; Johnson, S; Ni, Y; Marlow, N; Wolke, D; Khan, K; Petrou, S (Wiley, 2022)
Background: Preterm birth is associated with adverse health and developmental sequelae that impose a burden on finite resources and significant challenges for individuals, families and societies.